An Analysis of Challenges and State of the Art for Modular Engineering in the Machine and Plant Manufacturing Domain. Issue 10 (2015) - Feldmann, Stefan; Legat, Christoph; Vogel-Heuser, Birgit
Abstract: The increasing challenge to manufacture individual products in short periods of time makes a huge amount of machine and plant variants necessary and increases the effort in engineering as well as managing the variability. An adequate support system for modular engineering would increase reuse of variable parts of the machine or plant and, by that, enhance the engineering efficiency. Nevertheless, such a holistic support system is not yet available. This paper analyses the challenges to be addressed and derives a problem model to be investigated for future research to improve the engineering of modular machines and plants.